Criminal Responsibility for Parties Involved in Online Prostitution - Mochammad Iqbal Iz'za Zidane; Budiarsih Budiarsih (Activa Yuris: Jurnal Hukum, 2024)
Fulfilling the needs of life is important for every human being because of the need for work, the choice of negative work makes individuals not care about the causes and consequences, the most important thing is how their life needs are fulfilled. For this reason, one of the jobs that online prostitution is one of the jobs that involves meeting the needs of human life easily. Online prostitution itself has become a common thing in the life of the community environment, basically online prostitution itself is one of the activities that has many negative impacts on a person's life. The focus of this research is on how the criminal liability of the parties related to online prostitution where an act of online prostitution activity is one of the phenomena where this is very easy to spread and also very complex in the world of the existing digital era so that in the context of a criminal law that is used to be able to provide the existence of a criminal liability that exists to the party who is involved in the online prostitution activity itself. This research uses the Normative Juridical method with the Law approach and conceptual approach. The results of this study found that the criminal liability of the parties involved in online prostitution if the parties meet the elements in the Criminal Code rules or outside the Criminal Code which regulates online prostitution. The parties involved in online prostitution can be subject to sanctions if online prostitution is carried out in areas where there are local regulations on prostitution. The conclusion that the criminal liability of the parties involved in the online prostitution case itself will depend on the facts that have been found so that this law is designed to be able to provide protection to the community and also provide punishment to individuals who are involved in this illegal act.